Pendampingan Pembuatan Disinfektan dan Pembersihan Lingkungan dalam Upaya Pencegahan Covid-19 di Kelurahan Parit Padang Kecamatan Sungailiat Kabupaten Bangka - Occa Roanisca; Robby Gus Mahardika; Nosa Mayasani (Fakultas Teknik, Universitas Bangka Belitung, 2021)
Parit Padang is a sub-district located in Sungaliat District, Bangka Regency, Bangka Belitung Islands Province. Parit Padang Village is in the middle of the city of Sungailiat, where the spread of covid-19 will spread faster. In order to prevent covid-19, the students of the Parit Padang Community Service Program at Bangka Belitung University conducted socialization on how to make disinfectants and clean the environment. The method of KKN UBB activities is in the form of socialization and direct practice to the target community. The result of the UBB Community Service Program is that the community understands how to prevent COVID-19 by using disinfectants to clean the surface of objects that are often physically contacted, and understand how to make disinfectants. The environmental cleaning activities of Parit Padang were carried out with the residents. The Parit Padang community really welcomes the mutual cooperation activities carried out with UBB KKN students.